Laparoscopic extra-abdominal suturing technique for the repair of Larrey's diaphragmatic hernia using the port closure needle (Endo Close®): A case report. (2016) - Yamamoto, Yuji; Tanabe, Kazuaki; Hotta, Ryuichi; Fujikuni, Nobuaki; Adachi, Tomohiro; Misumi, Toshihiro; Saeki, Yoshihiro; Takehara, Hiroki; Ohdan, Hideki
Highlights: Larrey's diaphragmatic hernia is relatively uncommon. It is difficult to suture the hernial orifice laparoscopically. Extra-abdominal suturing technique using Endo Close ® may be useful in terms of secure suture and easy tying. Abstract: Introduction: Morgagni's or Larrey's diaphragmatic hernias are relatively uncommon. If the defect is too large for primary closure, the use of a mesh is inevitable. Although primary closure is adaptable for relatively small defects, it is difficult to suture the hernial orifice in which the anterior rim is absent. Herein, we present the case of a patient with Larrey's diaphragmatic hernia that was easily and securely repaired using the recently developed laparoscopic extra-abdominal suturing technique via the port closure needle (Endo Close ® ; Medtronic, Minneapolis, USA). Presentation of case: An 89-year-old woman complaining of vomiting was transferred to our hospital. Computed tomography scan showed Larrey's diaphragmatic hernia. Laparoscopic repair was performed after gastric decompression. We diagnosed Larrey's hernia on the left side of the falciform ligament. The transverse colon was herniated through the defect. Since the hernial defect was located below the substernal space, there was no tissue to stitch at the anterior rim of the hernial orifice. We performed the extra-abdominal suturing technique, suturing the posterior rim of the hernia to the full thickness of the anterior abdominal wall using the port closure needle (Endo Close ® ) without the need for a mesh. The patient was discharged on the 8th postoperative day. There was no evidence of recurrence at 8 months postoperatively. Discussion: The recently developed extra-abdominal suturing technique using Endo Close ® to suture the full thickness of the anterior abdominal wall achieved secure mattress suture and easy extra-abdominal tying. Conclusion: This method may be useful in terms of easiness and security of suture.